Communication Strategies Performed in an English as Lingua Franca Context and Their Contributions Toward Students' Engagement - Shofiya, Arina; Basuni, Muh (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
Learning language is learning to communicate in spoken and written form. However, learning to speak can be difficult due to a lack of linguistic resources. The students may encounter problems in communicating ideas and thus, it ends in a communication breakdown. To overcome this problem, some communication strategies like message abandonment and fillers can be used. Furthermore, communication strategies can foster students’ engagement in classroom interaction, especially in an English as Lingua Franca (ELF) context. The present study was intended to explore how the communication strategies were performed in the context of ELF and the contribution of strategies to the students’ engagement. Using a qualitative descriptive design, the present research investigated students’ communication strategies in an international class. The findings revealed that communication strategies were creatively performed in a variety of ways. The strategies were proven to be contributive in fostering engagement by increasing students’ self-confidence, boosting their self-respect, and pushing the students to be active during classroom interaction.